Study on Preparation and Properties of Sintered Brick from Multi-Source Solid Waste - Chen Guo; Jiafeng Kong; Zhenghua Wang; Xiangbin Meng; Yuchao Zhao; Wenhao Wu; Hongzhu Quan (Applied Sciences, 2022)
The recycling of construction waste and the use of a new sintering process in the field of sintered bricks can greatly solve the problems of clay resource depletion, soil structure destruction, and high CO2 emissions that always limit the development of the sintered brick field. The study was carried out using an orthogonal experiment to derive the optimal mix ratio for the preparation of sintered bricks, and subsequently, the sintered bricks were prepared using the optimal mix ratio. The experimental results show that the maximum compressive strength of construction waste sintered brick (MRB sintered brick) prepared using high-temperature sintering is 8.1 MPa, and the water absorption is 11. When the waste glass slag is mixed with 10%, it can show a better fluxing effect in the preparation of sintered bricks by mixing construction waste with waste glass slag (MGB sintered bricks), so that the MGB sintered bricks have a higher densification. The compressive strength is 32.9% higher and the water absorption is 3.5% lower than that of MRB sintered brick. MGS sintered bricks were prepared by mixing Yellow River sedimentary sand into MGB sintered bricks. The strength of MGS sintered bricks increased with the replacement rate of Yellow River sedimentary sand, and when the replacement rate of Yellow River sedimentary sand reached 16%, the strength of the MGS sintered bricks increased by 88.9%, and the water absorption rate was reduced by 4.6% compared with the MGB sintered bricks. The sintering mechanism had significant effects on the compressive strength, weathering resistance, and frost resistance of the sintered brick. The microwave sintering process has the characteristics of high efficiency, uniform heating, selective heating, and low thermal inertia, which can increase the compressive strength of MGS sintered brick by 4.6%, reduce the water absorption by 12.9%, shorten the sintering time by 43.6%, and improve the frost resistance.